Determination of Palladium by Ultrasonic Nebulization Coupled to ICP-OES After On-line Preconcentration on Activated Carbon - Cerutti, Estela Soledad (2005)
A system for the on-line preconcentration and determination of palladium by ultrasonic nebulization (USN) coupled to inductively coupled plasma optical emission spectrometry (ICP-OES) was studied. It is based on the chemical sorption of palladiumthiocyanate complex on a conical minicolumn packed with activated carbon (AC). The proposed procedure allowed the determination of palladium with a detection limit of 10 ng/L. The precision for 10 replicate determinations at the 500-ng/L Pd level was 2.9% relative standard deviation (RSD), calculated from the peak heights obtained. The calibration graph using the preconcentration system for palladium was linear with a correlation coefficient of 0.9995 at levels near the detection limits up to at least 100 µg/L. A total enhancement factor of 375-fold was obtained with respect to ICPOES using pneumatic nebulization (15 for USN and 25 for preconcentration). A sampling frequency of 20 samples per hour was obtained. The effect of other ions in concentrations agreeing with water samples was studied. The addition/recovery experiments in the samples analyzed demonstrated the accuracy and applicability of the system for the determination of palladium in tap water samples.